Participatory research with carers: A systematic review and narrative synthesis - Bryher Bowness; Claire Henderson; Samia C. Akhter Khan; Mia Akiba; Vanessa Lawrence (Wiley, 2024)
Abstract Introduction As patient and public involvement (PPI) in research has become increasingly common, research‐based recommendations on its principles and impacts have been established. The specifics of conducting PPI are likely to differ when involving different groups. Family/informal carers for those with health conditions or disabilities have a lot to contribute to research, but instances of their involvement have yet to be reviewed. Objective To systematically review and synthesize studies where family/informal carers have been involved in the research process, to develop an understanding of the benefits, barriers and facilitating factors. Methods A search of five electronic databases was conducted using a combination of terms relating to carers, involvement and research. A grey literature search, expert consultation and hand‐searching were also used. Following screening, data extraction and quality assessment, a narrative synthesis incorporating thematic analysis was conducted. Findings A total of 55 studies met the inclusion criteria, with diverse design and participatory approaches. Four themes were identified, relating to the outcomes, challenges, and practicalities of involving carers: (re) building relationships with carers; carers as equals not afterthoughts; carers have unique experiences; carers create change. Full involvement throughout the research was not always possible, due to barriers from the research world and responsibilities of the caring role. The literature demonstrated ways for carers to contribute in ways that suited them, maximizing their impact, while attending to relationships and power imbalances. Conclusion By summarizing the reported instances of carer involvement in research, this review brings together different examples of how successful research partnerships can be built with carers, despite various challenges. Carers are a heterogeneous group, and participatory approaches should be tailored to specific situations. Wider understanding of the challenges of conducting empowering research with carers, and the resources required to address these, are needed. Patient and Public Involvement The initial findings and themes were presented to a group of carers who had been involved in research and whose reflections informed the final synthesis.